Atrioventricular nodal reentrant tachycardia onset, sustainability, and spontaneous termination in rabbit atrioventricular node model with autonomic nervous system control - Ryzhii, Maxim; Ryzhii, Elena (Frontiers in Physiology, 2025)
Atrioventricular nodal reentrant tachycardia (AVNRT) is one of the most common types of paroxysmal supraventricular tachycardia. The activity of the autonomic nervous system (ANS) is known to influence episodes of AVNRT, yet the precise mechanisms underlying this effect remain incompletely understood. In this study, we update our compact multifunctional model of the rabbit atrioventricular (AV) node with ANS control to simulate AVNRT. The refractoriness of the model cells is adjusted by a specific ANS coefficient, which impacts the effective refractory periods, conduction delays, and intrinsic frequency of pacemaker cells. Using this model, we investigate the onset, sustainability, and spontaneous termination of typical slow-fast and atypical fast-slow forms of AVNRT under ANS modulation. The conditions for the onset and sustainability of AVNRT can exist independently in various combinations. Differences in the effective refractory periods of the slow and fast pathways of the AV node during anterograde and retrograde conduction determine the specific form of AVNRT. For the first time, a computer model reveals the potential to identify hidden processes within the AV node, thereby bringing us closer to understanding the role of ANS control in AVNRT. The results obtained are consistent with clinical and experimental data and represent a novel tool for studying the electrophysiological mechanisms behind this type of arrhythmia.